A Socio-Cultural Change in Saudi Arabia through the Lens of Comedy: An Analysis of the Film 'Crashing Eid' - Solihat, Ade (Journal of Art, Film, Television, Animation, Games and Technology, 2025)
This article analyzes the Saudi Arabian film "Crashing Eid," released in 2023. The research aims to describe how Saudi Arabian society uses film as a medium to communicate socio-cultural change. Through content analysis of the film, this study explores the plots and characters that depict the discourse of current issues and how Saudi Arabian society, known for its adherence to customs, faces various socio-cultural problems. Additionally, a narrative analysis was conducted by examining dialogues that reveal the cultural negotiations taking place. The article presents findings on the reflective efforts of Saudi Arabian society toward issues of racism and their attempts to negotiate with modernity through comedy films. The phenomenon of socio-cultural change depicted in this film also illustrates Giddens' theory of socio-cultural change, particularly the duality of structure and agency that are interrelated in constructing a new, more open face of Saudi Arabia.